Does Nasal Obstruction Induce Obstructive Sleep Apnea in Healthy Women? - Pittaway I (Dove Medical Press, 2020)
Islay Pittaway,1 Anna Ishkova,1 Helena Bean,1 Stephanie McCarthy,1 Isabella Lay,1 Joanne Avraam,1 Andrew Dawson,1 Therese Thornton,1 Christian L Nicholas,1,2 John Trinder,1 Fergal J O’Donoghue,2,3 Melinda L Jackson,2,4 Amy S Jordan1,2 1Melbourne School of Psychological Sciences, The University of Melbourne, Parkville, VIC 3010, Australia; 2Institute for Breathing and Sleep, Austin Health, Heidelberg, VIC 3084, Australia; 3Department of Medicine, The University of Melbourne, Austin Hospital, Heidelberg, VIC 3084, Australia; 4Turner Institute for Brain and Mental Health, School of Psychological Sciences, Monash University, Clayton, VIC 3164, AustraliaCorrespondence: Amy S Jordan Tel +61 3 8344 6357Email ajordan@unimelb.edu.auPurpose: Obstructive sleep apnea (OSA) is less prevalent among women and is associated with different symptoms and consequences to OSA in men. The reasons for these differences are unknown and difficult to tease apart in clinical populations. If OSA could be temporarily induced in healthy men and women, the causes of some of these differences could be investigated. Nasal blocking has been used to induce OSA in healthy men but its effect in women has not been reported.Patients and Methods: A total of 14 healthy individuals (10 women) underwent in-laboratory diagnostic sleep studies on two occasions separated by a week. On one occasion, the nasal passages were blocked, whereas on the other occasion, participants slept naturally. In both conditions, a full-face mask was used to monitor respiratory events. Participants’ self-reported sleepiness, mood and performance on a motor learning task were assessed in the evening and morning of both sleep studies. Furthermore, endothelial function and self-reported sleep quality were assessed in the morning following each study.Results: Nasal blockage induced OSA in healthy young (age=22± 3 years) and slim (BMI=22.2± 3.2 kg/m2) women (control AHI=2.0± 2.6, blocked AHI=33.1± 36.7 events/hr, p=0.02). One night of OSA was associated with poorer self-reported sleep quality (p< 0.001) and increased self-reported snoring (p< 0.04), choking and gasping during sleep (p< 0.001) but was not associated with alterations in mood, neurocognitive or endothelial function on the following morning.Conclusion: Nasal blockage induces OSA in healthy, young, and normal weight women. However, whether the induced OSA is representative of naturally occurring OSA and the technique useful for future studies is unclear.Keywords: pathophysiology, upper airway collapse, sex, breathing route, obstructive sleep apnea, nasal blockage, female